Validity And Reliability Of Lupus Quality Of Life Questionnaire In Patients With Systemic Lupus Erythematosus In Indonesia - Bagus Anindito; Rudy Hidayat; Sukamto Koesnoe; Esthika Dewiasty (Indonesian Rheumatology Association, 2016)
Background: The development of Systemic Lupus Erythematosus (SLE) treatment has led the increased of patients survival. Quality of life has became a value based medicine component that should be evaluated in treating SLE. One standardized questionnaire to asses the quality of life in SLE patients is Lupus Quality of Life (Lupus QoL). Currently, in Indonesia, there has not been any spesific questionnaire to asses the quality of life in SLE patients. This study aims to prove that Lupus QoL is valid and reliable to asses the quality of life in SLEpatients in Indonesia.Methods: This study used cross sectional study method. Firstly, we translated the Lupus QoL into Indonesian language, then we tested to 10 respondents. Then, we continued the study with larger sample size. We analyzed the reliability of the test and the re-test result using the interclass coefficient correlation and the internal consistency of the tests using cronbach alpha. Construct validity was evaluated using multi trait scaling analysis and the extrenal validity was evaluated using correlation between domains in short form 36 (SF 36)with Lupus QoL and with disease activity.Results: Data collection was done to 65 SLE patients between October – November 2015 in RSCM. The test has good external validity SF 36 (r=0.38-0.66, p<0.05) and good construct validity (r >0.4; range: 0.44-0.93). The ICC value in one week >0.7 and Cronbach α was>0.7 in each domain. The correlation between lupus QoL and the disease activity was weak and consistentwith other studies.Conclusion: Lupus QoL questionnaire is valid and reliable to asses the quality of life in SLE patients inIndonesia.Key words: Quality of Life, Systemic Lupus Erythematosus, Lupus QoL, Validity, Reliability